2015
DOI: 10.1038/nrn3976
|View full text |Cite
|
Sign up to set email alerts
|

The neuroscience of placebo effects: connecting context, learning and health

Abstract: Placebo effects are beneficial effects that are attributable to the brain–mind responses to the context in which a treatment is delivered rather than to the specific actions of the drug. They are mediated by diverse processes — including learning, expectations and social cognition — and can influence various clinical and physiological outcomes related to health. Emerging neuroscience evidence implicates multiple brain systems and neurochemical mediators, including opioids and dopamine. We present an empirical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

15
591
1
44

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 649 publications
(651 citation statements)
references
References 219 publications
(318 reference statements)
15
591
1
44
Order By: Relevance
“…The rACC plays a key role in cortical control of the brainstem during both opioid and placebo analgesia [17,18]. The brainstem opioid system consists of a network of regions, including the PAG and RVM [15,16].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The rACC plays a key role in cortical control of the brainstem during both opioid and placebo analgesia [17,18]. The brainstem opioid system consists of a network of regions, including the PAG and RVM [15,16].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, studies of pain control have shown that the ACC plays a key role in cortical control of the brainstem opioid system, which comprises the periaqueductal grey (PAG) and the rostral ventromedial medulla (RVM) [14][15][16], during both opioid and placebo analgesia [17,18]. These neural structures constitute the descending pain modulatory system (DPMS) [19].…”
mentioning
confidence: 99%
“…The recent explosion of placebo research and the shift in conceptualization of the placebo effect in several medical conditions, such as pain and motor disorders, makes us understand that their psychological and neurobiological underpinnings can be investigated in some detail. Indeed, what we have learned over the past few years is that different brain mechanisms are at work during the placebo response (Benedetti, Amanzio, Rosato, & Blanchard, 2011; Benedetti, Carlino, & Piedimonte, 2016; Wager & Atlas, 2015). …”
mentioning
confidence: 99%
“…when a therapeutic ritual is performed. By using this neuroscientific approach, the placebo effect represents an excellent model to understand how the human brain works (Benedetti, 2014; Wager & Atlas, 2015) and may have profound implications for both medical practice and clinical trials (Benedetti et al, 2016). …”
mentioning
confidence: 99%
See 1 more Smart Citation